Oral health condition and complications in pediatric cancer patients undergoing chemotherapy - A cross-sectional study - V Pranitha; C Meghana; K S Dwijendra; S V Ravindra; P B N Mounika; P Uma Ramana (Wolters Kluwer Medknow Publications, 2022)
Background: Better knowledge of the prevalence of oral complications in children with malignancy improves oral health through an interdisciplinary approach between oncologists and pediatric dentists. Aim: This study aimed to assess the prevalence of oral health status in pediatric cancer patients to palliate and relieve the discomfort. Materials and Methods: This study was conducted in a cancer hospital in Hyderabad for 10 days. 158 patients aged [1-15 yrs] diagnosed with malignancy and receiving chemotherapy were selected and evaluated with a self-validated questionnaire followed by oral examination. Results: The data collected was processed and analyzed using the SPSS22 version [Corporation (IBM), Washington, DC., USA]. Mucositis 47% was the most common complication, followed by gingivitis 23.9%, xerostomia 12%, oral pain 11.6%, herpes 3%, and candidiasis 1.8%. Conclusion: Oral care of pediatric cancer patients is of critical importance in maintaining the patient's overall well-being, which can be achieved by a systematic approach at different stages of treatment.